Emotional analysis of Surah Yusuf in the argumentative discourse in light of Christine Plantin’s theory: تحلیل پاتوس در گفتمان حجاجی سورۀ یوسف براساس نظریۀ کرستیان پلانتین (Journal of the College of Languages (JCL), 2025)
One of the uses of language to influence others is to argue. Arguments are used to persuade the audience because they try to convince the audience that this thinking is correct or in their favor. The third model in the researches of this theory, which is an extension of Chaim Perelman researches in the direction of reviving Aristotelian rhetoric, examines the reasoning within a discourse. Influence on the audience is being analyzed and categorized. Since the Holy Qur'an contains discourses centered on topics such as: denial of polytheism and idolatry, call to monotheism, call to justice, denial of corruption on earth, etc., we can consider the text of the Holy Qur'an as an argumentative discourse that In this article, we will analyze the manifestation of pathos in Surah Yusuf according to the theory of Christian Plantin. The results of the research show that arousing emotions such as: fear, love, compassion, etc., play an important role in the process of this story. in persuading the audience.چکیدهیکی از کاربردهای زبان در جهت تأثیرگذاری بر دیگری استدلال کردن است. استدلال‌ها در جهت اقناع مخاطب به کارمی‌روند زیرا سعی دارند مخاطب را قانع کنند که این تفکر درست است و یا به نفع اوست. الگوی سوم در پژوهش‌های این نظریه که امتداد پژوهش‌های شاییم  پرلمن در راستای احیای بلاغت ارسطویی است، به بررسی استدلال درون یک گفتمان می‌پردازد.در این رویکرد به بررسی مسأله انواع گفتمان‌ها در رابطه با استدلال پرداخته و روش‌هایی که گفتمان شفاهی و مکتوب از طریق آن سعی در تأثیر گذاری در مخاطب دارد  مورد تدقیق و دسته بندی قرارمی‌گیرد. از آنجا که قرآن کریم در بردارندۀ گفتمانهایی با محوریت موضوعاتی همچون: نفی شرک و بت پرستی،دعوت به توحید، دعوت به عدل،نفی فساد بر روی زمین و...است،می توان متن قرآن کریم را گفتمانی استدلالی قلمداد کنیم که در پی اصلاح گری است.در این مقاله بر آنیم تجلی پاتوس را در سورۀ یوسف طبق نظریۀ کریستیان پلانتین مورد تحلیل قراردهیم.نتایج پژوهش نشان می‌دهد برانگیختن عواطفی مانند: ترس، محبت، دلسوزی و..نقش مهمی در روند این داستان نقش مهمی در اقناع مخاطب داشته است.